Pengaruh Kinerja Keuangan Bank Terhadap Koefisien Respon Laba Melalui Investment Opportunity Set (Studi Kasus pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2011-2016) - Atti Rasnawati (J-MAS (Jurnal Manajemen dan Sains), 2020)
This research raises the issue of banking performance including Risk Profile, Good Corporate Governance, Earning and Capital (RBBR or RGEC). Profit achieved by a company is a measure of performance and is considered by investors or creditors in making decisions to make investments or to provide additional credit. The low quality of earnings will make the decision making mistakes of the users such as investors and creditors, so that the value of the company will decrease. Earnings quality will be measured by using earnings response coefficient. Low The earnings response coefficient shows that earnings are less informative or in other words less qualified for investors to make economic decisions. The purpose of this study was to examine and determine the EFFECT of the Bank's Financial Performance on the Coefficient of Earnings Response through the Investment Opportunity Set. The analysis tools used include CAR, NPL, LDR, NIM, and GCG for bank financial performance. Then MBVE for investment opportunity set and for KRL using CAR, EU and RT. The results of this study indicate that the bank's financial performance has a positive and insignificant effect on the earnings response coefficient and earnings response coefficient can be explained by the bank's financial performance of 28.5% and the remaining 71.5% is explained by other variables outside the financial performance of the bank under study. Then the bank's financial performance has a negative and significant effect on the investment opportunity set and the earnings response coefficient can be explained by the bank's financial performance of 10.1% and the remaining 89.9% is explained by other variables outside the financial performance of the bank under study. Furthermore, the investment opportunity set has a positive and significant effect on the earnings response coefficient and the earnings response coefficient can be explained by an investment opportunity set of 26.4% and the remaining 73.6% is explained by other variables outside the financial performance of the bank under study.